The effect of sleep on the normal functioning of the prostate gland: A review - Anton V. Ershov; Mariia N. Grosheva; Sona V. Stepanyants; Andrei V. Yakovlev (ZAO "Consilium Medicum", 2023)
The article provides an analysis of current information on the effect of sleep, namely its main element, melatonin, on the functioning of the prostate gland. The direct action of melatonin as a local modulator of the endocrine activity of Sertoli and Leydig cells and its effect on energy metabolism are described. The main biochemical antioxidant properties of melatonin are reflected, as well as the mechanisms of its action on the hormonal system of the body: metabolism, fertility and anticarcinogenicity. The results of studies on the relationship between sleep disorders, the role of the circadian rhythm in fertility disorders and prostate diseases are disclosed. The relationship between the presence of metabolic syndrome and the subsequent risk of developing benign prostatic hyperplasia is presented.